Clinical features of overweight in acute-phase hospitalised major depressive disorder with comorbid anxiety: a cross-sectional study - Jing Wang; Hong Zhang; Xuebing Liu; Wenting Zhu (BMJ Open)
Objective This study aimed to investigate the incidence of overweight in patients with major depressive disorder (MDD) comorbid anxiety during the acute phase and to explore associated factors.Design Cross-sectional study.Setting Wuhan Mental Health Center, China, from July 2017 to August 2022.Participants 737 hospitalised patients diagnosed with MDD in the acute phase with comorbid anxiety symptoms.Primary outcome measures Incidence and clinical correlations of overweight (body mass index (BMI) ≥ 24).Results Among the study population, 55.63% were classified as overweight. Binary logistic regression analysis revealed that being married (B=0.28, p value=0.018, OR=1.10), thyroid-stimulating hormone (TSH) levels (B=0.10, p value=0.001, OR=1.10) and low-density lipoprotein cholesterol (LDL-C) levels (B=1.61, p value=0.045, OR=1.18) were significant positive predictors of overweight. Additionally, multiple linear regression indicated that TSH levels (B=0.16, t=3.17, p value=0.002) were positively associated with higher BMI values.Conclusion Over half of the hospitalised MDD patients with comorbid anxiety are overweight. Thyroid function emerges as a crucial clinical factor for overweight in this population. Targeted interventions focusing on thyroid function may be a promising approach for managing overweight in these patients.